2001
DOI: 10.1159/000049314
|View full text |Cite
|
Sign up to set email alerts
|

Worry and Anxiety: Is There a Causal Relationship?

Abstract: The aim of this study was to examine the relationship between worry and anxiety and depression. Path analysis was used to estimate a nonrecursive model which describes the reciprocal causal relation between worry and anxiety. The final model fits the data well and leads to the conclusion that the association between these two constructs is not bidirectional. Indeed, we observed a significant positive effect of worry on anxiety, but no effect in the opposite direction. This result provides a supporting argument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 42 publications
3
40
0
2
Order By: Relevance
“…The worry induction and its successful impact on subjective emotional reports differentiated anxious from non-psychiatric participants as well as characterized the pre-to post-treatment differences in our anxious participants. Consistent with the directional influence of worry on negative emotion, path analysis supports a stronger influence of worry on anxious feelings rather than the reverse direction (Gana et al, 2000). The findings support the importance of physiological data, and especially EEG gamma power, for studying affective symptoms in psychiatric patients and also to monitor fluctuations in affective symptoms expected to follow successful treatment.…”
Section: Discussionsupporting
confidence: 68%
“…The worry induction and its successful impact on subjective emotional reports differentiated anxious from non-psychiatric participants as well as characterized the pre-to post-treatment differences in our anxious participants. Consistent with the directional influence of worry on negative emotion, path analysis supports a stronger influence of worry on anxious feelings rather than the reverse direction (Gana et al, 2000). The findings support the importance of physiological data, and especially EEG gamma power, for studying affective symptoms in psychiatric patients and also to monitor fluctuations in affective symptoms expected to follow successful treatment.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, individuals with GAD, a disorder defined by persistent worry, endorsed more physical symptoms of anxiety, such as trembling, restlessness, fatigue, tension, and shortness of breath compared to controls and individuals with Social Phobia (Hoyer, Becker, & Roth, 2001). Of most theoretical relevance, a path analysis examining the causal relationship between worry and anxiety suggested that worry predicted anxious arousal, whereas anxiety did not predict worry (Gana, Martin, & Canouet, 2001).…”
mentioning
confidence: 98%
“…Verkuil, Brosschot, Putman, and Thayer (2009) used a similar experimental design and showed that the combination of high anxiety and worry was able to predict attentional disengagement. Besides the high correlation between worry and anxiety, it has been shown by path-analytic models that worry causally influences anxiety (Gana, Martin, & Canouet, 2001). To further underline the importance of worry for anxiety, it has been proposed that worry might be the component of anxiety that is responsible for the observed problems in disengagement (Eysenck, Derakshan, Santos, & Calvo, 2007).…”
Section: Introductionmentioning
confidence: 99%